Quality Management Systems a Selective Presentation of Case-studies Showcasing Its Evolution - Kounis, Leo D. (IntechOpen, 2018)
Quality management systems form an integral part of modern corporations. Acknowledging current socio-economic and environmental challenges, quality standards ought to be dynamic and flexible so as to cater for different markets and requirements. This book portrays a collection of international papers addressing current research and practice within the areas of engineering and technology, health and education. Amidst striving for "zero defects", "cost-effectiveness" and "tight financial budgets", quality management systems ought to embrace the creator of them all: humans; as the ancient Greek Sophist Protagoras said, "Of all money, Man is the measure" «Πάντων χρημάτων Μέτρον Άνθρωπος» (Plato, Theaetetus 166d).